(untitled) (Annals of Medical Research, 2021)
Aim: Road traffic accidents are common in our country, but there are not many scientific studies related to childhood road traffic accidents. We aimed to report the frequency of road traffic accidents in children, the demographic characteristics of the patients, the physical effects of accidents on children and their results.Material and Methods: Study data were obtained by retrospective screening of the files of pediatric cases presenting to our emergency department because of road traffic accident between September 2017-2018. The cases were evaluated in terms of age, gender, type of accidents, type of injury, radiologic imaging rates, hospitalization and mortality rates.Results: 377 cases were reviewed. 136 (36.1%) patients were female and 241 (63.9%) were male. 36.9% (n=139) of the admissions were in summer. According to the occurrence of accidents, in-vehicle traffic accidents constituted 61.8% (n=233) of the cases. Among isolated injuries the most common site of injury was head and neck region (n=120, 31.8%). In 81.4% (n=307) of the cases tomography, in 72.1% (n = 273) of cases X-ray, in 25.7% (n=96) of cases ultrasound were requested. 270 (72.2%) patients were discharged from the emergency department with the diagnosis of soft tissue trauma. 58 (15.4%) patients were hospitalized in the respective clinics and 43 (11.4%) patients were hospitalized in the intensive care unit. It was detected that 8 patients (2.1%) died, 4 of them occurred in the emergency department. Conclusion: Pediatric road traffic accidents mostly occur in the summer and most of them are in-vehicle accidents. Boys are more exposed to road traffic accidents. Injuries in traffic accidents mostly locate in the head and neck regions followed by extremities. It was found that tomographic imaging was overused in our study. New strategies should be developed to reduce tomography overuse.